(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The incidence of ischemic stroke remains high in many countries, despite a declining trend in the incidence of brain circulation disorders. Limited knowledge of the pathogenesis, diagnosis, clinical presentation, and treatment of this life-threatening disease can be complemented by modelling of ischemic stroke on animals, particularly, in rodents.